2016
DOI: 10.1177/1473325016657867
|View full text |Cite
|
Sign up to set email alerts
|

Place and the uncanny in child protection social work: Exploring findings from an ethnographic study

Abstract: This article presents findings from an ethnographic study of child protection social workers in Britain, which explored social workers’ experiences of and practices in space and place. It draws on data from interviews with practitioners and observations that were carried out as social workers moved around the places (the town, estates, streets and areas around service users’ homes) where they worked. It focuses on the significance of a particular affective experience, the uncanny, which social workers evoked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…Its absence arose from how fear and anxiety cause the self to become defended, which stops reflection in action and how this is compounded by the absence of help with critical reflection afterwards in supervision (Ferguson, 2018). Nor did it seem thinkable that sometimes these involuntary clients could be seen somewhere other than in their home, whereas this did happen in some cases we observed that involved cooperative relationships as parents and children were seen in community centres, parks, cafes, or in cars (Jeyasingham, 2018). The emotional impact of hostile relationships paralysed workers and organisations, restricting their minds and actions, confining them in highly constricted spaces where they and parents effectively enacted pathological relationships, taunting and punishing one another.…”
Section: (Roberta -Final Interview)mentioning
confidence: 80%
“…Its absence arose from how fear and anxiety cause the self to become defended, which stops reflection in action and how this is compounded by the absence of help with critical reflection afterwards in supervision (Ferguson, 2018). Nor did it seem thinkable that sometimes these involuntary clients could be seen somewhere other than in their home, whereas this did happen in some cases we observed that involved cooperative relationships as parents and children were seen in community centres, parks, cafes, or in cars (Jeyasingham, 2018). The emotional impact of hostile relationships paralysed workers and organisations, restricting their minds and actions, confining them in highly constricted spaces where they and parents effectively enacted pathological relationships, taunting and punishing one another.…”
Section: (Roberta -Final Interview)mentioning
confidence: 80%
“…Вивчався емоційний, афективний досвід соціальних працівників щодо цих місць та мікрорайонів, де фахівці не завжди почували себе у безпеці, стосунків із людьми, від яких працівники відчували загрозу. Зрештою, було визначено, як цей негативний досвід впливає на потенціал працівників захищати дітей [15].…”
Section: вступunclassified
“…Elsewhere, social work research is now emerging which engages more broadly with affects and atmospheres. Jeyasingham (), for example, explores the affective experiences of a range of settings which are part of child protection social work including towns, neighbourhoods, and streets. In particular, the author describes the “uncanny” feelings of vulnerability and unease felt outside clients' homes and how mundane material features—such as windows—take on new potential for social workers.…”
Section: Moving Towards a Posthumanist Contributionmentioning
confidence: 99%
“…As part of the associated research endeavour, over recent decades, social work scholarship has drawn on, and deployed, various social science disciplinary perspectives, the closest engagement being with sociology (e.g., Heraud, ), but with political science (e.g., Gray & Webb, ), social psychology (e.g., Radey & Figley, ), economics (e.g., Gordon, ), and others being utilised to different extents, and in various ways. Despite this broad social science grounding, only occasionally however have there been explicit discussions of human geography in social work research and/or occasions where the discipline's ideas and conceptualisations have clearly been used (specifically—Carbone & McMillin, ; Galloway, Wilkinson, & Bissell, ; Hillier, ; Jeyasingham, , ; Schmidt, ; Wilkinson & Bissell, , , ; Zapf, , , , ), although, as we shall see, quite a lot of social work research is implicitly/loosely “geographical” in orientation.…”
Section: Introductionmentioning
confidence: 99%